Early neonatal mortality is modulated by gestational age, birthweight and fetal heart rate abnormalities in the low resource setting in Tanzania - a five year review 2015-2019 - Aisa Shayo; Pendo Mlay; Emily Ahn; Hussein Kidanto; Michael Espiritu; Jeffrey Perlman (BMC, 2022)
Abstract Background Early Neonatal mortality (ENM) (< 7 days) remains a significant problem in low resource settings. Birth asphyxia (BA), prematurity and presumed infection contribute significantly to ENM. The study objectives were to determine: first, the overall ENM rate as well as yearly ENM rate (ENMR) from 2015 to 2019; second, the influence of decreasing GA (< 37 weeks) and BW (< 2500 g) on ENM; third, the contribution of intrapartum and delivery room factors and in particular fetal heart rate abnormalities (FHRT) to ENM; and fourth, the Fresh Still Birth Rates (FSB) rates over the same time period. Methods Retrospective cohort study undertaken in a zonal referral teaching hospital located in Northern Tanzania. Labor and delivery room data were obtained from 2015 to 2019 and included BW, GA, fetal heart rate (FHRT) abnormalities, bag mask ventilation (BMV) during resuscitation, initial temperature, and antenatal steroids use. Abnormal outcome was ENM < 7 days. Analysis included t tests, odds ratios (OR), and multivariate regression analysis. Results The overall early neonatal mortality rate (ENMR) was 18/1000 livebirths over the 5 years and did not change significantly comparing 2015 to 2019. Comparing year 2018 to 2019, the overall ENMR decreased significantly (OR 0.62; 95% confidence interval (CI) 0.45-0.85) as well as infants ≥37 weeks (OR 0.45) (CI 0.23-0.87) and infants < 37 weeks (OR 0.57) (CI 0.39-0.84). ENMR was significantly higher for newborns < 37 versus ≥37 weeks, OR 10.5 (p < 0.0001) and BW < 2500 versus ≥2500 g OR 9.9. For infants < 1000 g / < 28 weeks, the ENMR was ~ 588/1000 livebirths. Variables associated with ENM included BW - odds of death decreased by 0.55 for every 500 g increase in weight, by 0.89 for every week increase in GA, ENMR increased 6.8-fold with BMV, 2.6-fold with abnormal FHRT, 2.2-fold with no antenatal steroids (ANS), 2.6-fold with moderate hypothermia (all < 0.0001). The overall FSB rate was 14.7/1000 births and decreased significantly in 2019 when compared to 2015 i.e., 11.3 versus 17.3/1000 live births respectively (p = 0.02). Conclusion ENM rates were predominantly modulated by decreasing BW and GA, with smaller/ less mature newborns 10-fold more likely to die. ENM in term newborns was strongly associated with FHRT abnormalities and when coupled with respiratory depression and BMV suggests BA. In smaller newborns, lack of ACS exposure and moderate hypothermia were additional associated factors. A composite perinatal approach is essential to achieve a sustained reduction in ENMR.